1958
DOI: 10.1111/j.1748-1716.1958.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Contractile Mechanism in Striated Muscle

Abstract: Summary. When a frog's striated muscle (m. sartorius) is immersed in Ringer solution containing 2.5–10 × 10–4 w/v of the free base caffeine tension develops and the muscle contracts. The contracture is graded according to dose and reverses rapidly upon removal of the drug. Higher concentrations of caffeine produce an irreversible contracture. In a muscle immersed in isotonic K2SO4 or KCl solution caffeine produces exactly the same kind of muscle contracture as in a muscle kept in Ringer's fluid. Prolonged so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
0

Year Published

1963
1963
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(105 citation statements)
references
References 7 publications
13
92
0
Order By: Relevance
“…8 Taylor (1953), Axelsson & Thesleff (1958), and Conway & Sakai (1960) showed that the external application of 1-3-5 mm caffeine in Ringer's solution to frog muscle fibres could cause a contraction with little or no accompanying depolarization of the fibre membranes. Caffeine contractions were also obtained with fibres which had been previously depolarized in high-potassium solutions, when such fibres were treated with highpotassium solutions containing caffeine (Axelsson & Thesleff, 1958;Conway & Sakai, 1960 (1958) attempted to apply caffeine internally to the fibres they came to the conclusion that the internal application did not cause contraction.…”
Section: Resultsmentioning
confidence: 99%
“…8 Taylor (1953), Axelsson & Thesleff (1958), and Conway & Sakai (1960) showed that the external application of 1-3-5 mm caffeine in Ringer's solution to frog muscle fibres could cause a contraction with little or no accompanying depolarization of the fibre membranes. Caffeine contractions were also obtained with fibres which had been previously depolarized in high-potassium solutions, when such fibres were treated with highpotassium solutions containing caffeine (Axelsson & Thesleff, 1958;Conway & Sakai, 1960 (1958) attempted to apply caffeine internally to the fibres they came to the conclusion that the internal application did not cause contraction.…”
Section: Resultsmentioning
confidence: 99%
“…The 693 height of contraction is quantitatively related to the ratio [Ca]0 :[Na]l (Wilbrandt & Koller, 1948). (5) Caffeine, added to Ringer's solution, can without depolarization produce contractures in twitch fibres (Axelsson & Thesleff, 1958), but not in the heart (Suzuki, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, it was found that the Ca 2ϩ -releasing action of IP 3 is also enhanced by Ca 2ϩ (14,69,97), and consequently, in the presence of a constant concentration of IP 3 , an increase in Ca 2ϩ concentration causes a further release of Ca 2ϩ from ER/SR through the IP 3 receptor. Thus the IP 3 receptor system exhibits an apparent CICR (12, 98 -100, 176, 250, 264, 274).…”
Section: Historymentioning
confidence: 99%